The hundreds - Berlant, Lauren Gail 1957-; Stewart, Kathleen 1953- (Duke University Press, 2019)
First things -- Swells -- Dilations -- Space junk -- You have to start somewhere -- This is vanilla -- Handyman -- Writing, life -- Red bull diaries -- As if -- Checked out OK -- Graduation speech, 2016 -- The new ordinary -- Contact sheet -- The things we think with -- Worlds -- Weight of the world -- Today in political emotions -- The road -- The state of drift -- On collaboration -- The icing on the cake -- Bad feelings -- Halloweens -- Take a breath -- Friction -- The game as method -- Once -- This isn't consoling -- In the middle -- Cover story -- In the cut -- What does Webster's say about soul? -- Against literal-minded explorations of the ordinary -- At the Y -- No world beyond the world -- Slide -- Two Elizas -- Keep it together -- Welcome to the joke -- The women -- Outside chances -- Writing lessons -- Fish in drag -- Suicidiation nation -- The morning demons -- A place -- A skeletal thought -- Utopian capitalism -- Chicago -- A return -- Stony Island story problems --